Ongoing initiatives within the Scottish National Health Service to affect the prescribing of selective serotonin reuptake inhibitors and their influence. (26th April 2019) - Godman, Brian; Kurdi, Amanj; McCabe, Holly; Johnson, Chris F; Barbui, Corrado; MacBride-Stewart, Sean; Hurding, Simon; Leporowski, Axel; Bennie, Marion; Morton, Alec
Aim: Increasing use of selective serotonin-reuptake inhibitors (SSRIs) in Scotland, coupled with safety concerns with some SSRIs, and the increasing availability of generic SSRIs, have resulted in multiple initiatives to improve the quality and efficiency of their prescribing in Scotland. Our aim is to assess their influence to provide future direction.Materials & methods:  The prescription costs analysis database was used to document utilization and expenditure on SSRIs between 2001 and 2017 alongside documenting the initiatives.Results: Multiple interventions over the years increased international nonproprietary name prescribing up to 99.9% lowering overall costs. This, coupled with initiatives to limit escitalopram prescribing due to concerns with its value, resulted in a 73.7% reduction in SSRI expenditure between 2001 and 2017 despite a 2.34-fold increase in utilization. Safety warnings resulted in a significant reduction in the prescribing of paroxetine, citalopram and escitalopram alongside a significant increase in sertralineConclusion: Multiple initiatives have increased the quality and efficiency of SSRI prescribing in Scotland providing direction to others.